Morphological alterations of cell wall concomitant with protein release in a protein-producing bacterium, Bacillus brevis 47. - Yamada, H (1981)
Bacillus brevis 47 secreted vast amounts of protein into the medium and had a characteristic three-layered cell wall. The three layers are designated, from the outermost to the innermost layer, as the outer wall (4.2 nm), the middle wall(8.5 nm), and the inner wall (2.1-3.7 nm). The inner wall might be a peptidoglycan layer. The fine cell wall structure was morphologically altered to various extents, depending on the growth period. At the early stationary phase of growth, cells began to shed the outer two layers of a limited area of the surface. This shedding was complete after further cell growth. The morphological alterations in the cell wall occurred concomitantly with a prominent increase in protein excretion. When protein secretion was severely inhibited by growing cells with Mg2+, morphological alterations in the cell wall were not observed, even at the late stationary phase of growth. This was also the case with a nonprotein-producing mutant, strain 47-5-25. When cells were incubated in buffers, the outer two layers of the cell wall were specifically removed, leaving cells surrounded only by the inner wall layer. The layers removed by incubation were recovered by high-speed centrifugation. This fraction consisted of two layers resembling the outer and middle wall layers. Protein secreted by B. brevis 47-5 consisted mainly of two proteins with approximate molecular weights of 150,000 and 130,000. Proteins released by incubating cells in buffers and proteins in the outer- and middle-wall-enriched fraction were also composed mainly of two proteins with the same molecular weights as those secreted into the medium. Therefore, we conclude that B. brevis 47 secretes proteins derived from the outer two layers of cell wall and these components are synthesized even after the shedding of the outer two layers.